Toxoplasma gondii genotyping in a dog co-infected with distemper virus and ehrlichiosis rickettsia - Moretti, Leandro D'Arc; Silva, Aristeu Vieira da; Ribeiro, Márcio Garcia [UNESP]; Paes, Antonio Carlos [UNESP]; Langoni, Hélio [UNESP] (FapUNIFESP (SciELO), 2006)
This paper reports a toxoplasmosis, erhlichiosis and distemper co-infection in a dog with an exuberant neuropathological clinical picture. Primary involvement was discussed based on information collected in the analysis of the clinical case, such as neurological impairment, epidemiological data, poor immunoprophylactic scheme of the dog affected and the role of these diseases on immunosuppression. Canine distemper and ehrlichiosis were diagnosed based on epidemiologic data, clinical signs, hematological and cytological evaluation. Toxoplasma gondii was isolated and genetically characterized as Type I using restriction analysis (RFLP) with SAG-2 genes. Immunosuppression features of both dogs and human beings are discussed, as well as implications on animal and public health. This is the first report on toxoplasmosis, ehrlichiosis and distemper co-infection in a dog in Brazil, associated with genotyping determination of the T. gondii strain involved.
Keywords: Co-infection; Distemper; Dogs; Ehrlichiosis; Genotyping; Immunosuppression; Restriction fragment length polymorphism (RFLP); Toxoplasmosis; Canine distemper morbillivirus; clinical examination; dog; ehrlichiosis; genotype; immunoprophylaxis; neurologic disease; nonhuman; Toxoplasma gondii; Animals; Dog Diseases; Fatal Outcome; Female; Genotype; Polymorphism, Restriction Fragment Length; Toxoplasma; Toxoplasmosis, Animal